Keeping our children safe: piloting a hospital-based home-visitation program in Israel - Ligat Shalev; Anthony Luder; Sivan Spitzer; Danna Krupik; Jumanah Essa-Hadad; Mary C. J. Rudolf (Israel Journal of Health Policy Research, 2022)
Abstract Background Unintentional childhood injuries are a leading cause of morbidity and mortality worldwide. Attempts to prevent child home injuries have rarely been implemented in hospital settings which present an important opportunity for intervention. The SHABI (‘Keeping our Children Safe; SHomrim Al BetIchut Yeladenu’) program recruits at-risk families presenting with child injury to the Emergency Department. Medical/nursing students conduct two home visits and provide safety equipment and guidance. The objective of this study was to investigate the impact of SHABI on participating families’ home-safety. Methods The pilot was conducted between May 2019 and March 2020 in northern Israel, an area with high child injury rates. Eligibility included families with preschool children who incurred a home injury. Home-safety was assessed by observation through the ‘Beterem’ checklist. Parents' views, knowledge, awareness of dangers and report of home injuries were assessed at the start of each visit. Results 352 of 773 eligible families agreed to be contacted. 135 participated, 98 completed both home visits. Significant improvement in home-safety items was observed 4 months after the first visit (14 [IQR12-16]) vs. (17 [IQR15-19]; p < 0.001), accompanied by an overall increase in home safety (Mean ± SD 71.9% ± 9.5% vs. 87.1% ± 8.6%; p < 0.001). 64% reported greater awareness of dangers, 60% affirmed home was safer, and 70% valued the equipment. No difference was found in the prevalence of injuries (14 of 98 families prior and 8 after the visit; p = 0.17). Home visitors reported benefiting from the experience of working with disadvantaged families. Conclusion The program, which included recruitment in a hospital emergency setting and use of healthcare students as home visitors, was successfully implemented and accompanied by significant improvement in home safety with a non-significant trend of child injury decrease.